2020
DOI: 10.1021/acs.jmedchem.0c00305
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of HSP90 Inhibitor–SN38 Conjugates for Targeted Drug Accumulation

Abstract: Herein, a series of HSP90 inhibitor−SN38 conjugates through ester and carbamate linkage in the 20-OH and 10-OH positions of SN38 were developed for improving the tumor-specific penetration and accumulation of SN38 via extracellular HSP90 (eHSP90)-mediated endocytosis. Mechanistic analyses confirmed that these novel conjugates could bind to eHSP90 and be selectively internalized into the tumor cells, which led to prolonged tumor regression in multiple models of cancer. Among all studied conjugates, compound 18b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Hsp90 is a molecular chaperone that is critical to the stability and function of many client proteins, some of whichfor example, the androgen receptorhave been causally linked to the pathogenesis of prostate cancer. Inhibition of the Hsp90 function can reduce the expression level of AR and influence AR signaling. , Previous studies have shown that extracellular Hsp90 (eHsp90) participates in the invasive and metastatic processes of various cancers. In addition, eHsp90 on the cell surface aggregates on the plasma membrane of tumor cells and triggers receptor-mediated endocytosis when bound by its ligands. , This characteristic allows the eHsp90 binder to be used as a targeting moiety for the design of small-molecule conjugates. Consequently, we hypothesize that tumor-specific blockage of androgen receptor signaling could be achieved by small-molecular conjugates that selectively target both Hsp90 and AR.…”
Section: Introductionmentioning
confidence: 99%
“…Hsp90 is a molecular chaperone that is critical to the stability and function of many client proteins, some of whichfor example, the androgen receptorhave been causally linked to the pathogenesis of prostate cancer. Inhibition of the Hsp90 function can reduce the expression level of AR and influence AR signaling. , Previous studies have shown that extracellular Hsp90 (eHsp90) participates in the invasive and metastatic processes of various cancers. In addition, eHsp90 on the cell surface aggregates on the plasma membrane of tumor cells and triggers receptor-mediated endocytosis when bound by its ligands. , This characteristic allows the eHsp90 binder to be used as a targeting moiety for the design of small-molecule conjugates. Consequently, we hypothesize that tumor-specific blockage of androgen receptor signaling could be achieved by small-molecular conjugates that selectively target both Hsp90 and AR.…”
Section: Introductionmentioning
confidence: 99%
“…SN‐38 was used as positive control. As shown in Figure 5, the results indicated that 10 nM of B7 arrested A549 cells in the G2 phase [18] . In contrast, 100 nM and 1000 nM of B7 blocked A549 cells in the S phase.…”
Section: Resultsmentioning
confidence: 74%
“…As shown in Figure 5, the results indicated that 10 nM of B7 arrested A549 cells in the G2 phase. [18] In contrast, 100 nM and 1000 nM of B7 blocked A549 cells in the S phase. And the blocking effect of B7 was much stronger than SN-38 at same concentration (1 μM).…”
Section: Resultsmentioning
confidence: 95%
“…However, the in vitro HSP90 binding affinity assay showed that conjugation of SNX-5422 with SN38 had negligible impacts on HSP90 activity, while conjugation of NVP-AUY922 with SN38 did not affect the binding affinity of the hybrids to HSP90, indicating that compounds 79 and 80 deserved further investigation, especially compound 79 , which showed strong cytotoxicity against A549 cells, HCT-116 cells, MIA-Paca-2 cells and human pancreatic cancer Capan-1 cells with IC 50 values of 56 nM, 22 nM, 46 nM and 36 nM, respectively. In addition, compound 79 also showed strong antitumor activity in HCT-116 tumor-bearing mice and Capan-1 tumor-bearing mice, indicating that compound 79 is a promising new candidate for cancer therapy [ 69 ].…”
Section: Modification Of Sn38 At C-20 Positionmentioning
confidence: 99%